Risk factors for pulmonary tuberculosis in health-care workers. Hospital Nacional Dos de Mayo. Lima, Peru - Contreras Camarena, Carlos (2019)
Objective: To determine the risk factors for pulmonary tuberculosis in health-care workers of the Hospital Nacional Dos de Mayo in Lima, Peru. Materials and methods: A case-control analytical study. The study population consisted of health-care workers of the Hospital Nacional Dos de Mayo in Lima, Peru, diagnosed with pulmonary tuberculosis. Epidemiological variables (age, sex, comorbidity, occupational group), ventilatory variables (airflow velocity, direction and pattern; closed ventilation system) and environmental variables (ultraviolet light, air conditioning) were collected. A univariate analysis was performed, and the relative risk was estimated by odds ratio and its corresponding 95 % confidence interval. Subsequently, a multivariate logistic regression predictive model was used step by step to identify the risk factors. A p value < 0.05 was considered meaningful. Results: The usual incidence rate of pulmonary tuberculosis was 348 per 100,000 health-care workers. The associated factors were airflow velocity less than 0.7 m/s, use of air-conditioning in hospital rooms, high levels of overcrowding (available space less than 2 m2/person), age less than 40 years, presence of at least one comorbidity, and hospital job time less than 20 years. Conclusions: High levels of overcrowding and hospital job time less than 20 years are important risk factors for active pulmonary tuberculosis in health-care workers of the Hospital Nacional Dos de Mayo.